PENERAPAN PEMBELAJARAN AKTIF TIPE KELOMPOK BELAJAR TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMP MUHAMMADIYAH 6 PADANG - Deni Suryani, Deni Suryani; Haryono, Yulna; Melisa, Melisa (STKIP PGRI Sumbar, 2014)
ABSTRACTResearch motivated by an understanding of mathematical concepts students are still low, students are less familiar and issued an opinion, avestion and ideas in the process of learning mathematics. Study aims to determine the studentsâ understanding of mathematical concepts by learning the types of groups active learning to studentsâ understanding of mathematical concepts class seven SMP Muhammadiyah 6 Padang. This type of research is experimental, with the design of the random penelitian subbjek. Technigue of random sampling 72 grade class was selected as the axperimental and control classes of 74 grade. Instruments used in this study is a test of understanding of mathematical concepts. Used form is the essay test and it was reliable. Data analysis techniques used were mann whitney test. Based on the results of the data analysis it is known that one of the classes are not normally distributed sample. Beconcluded that the studentsâ understanding of mathematical concepts by applying active learning study group type is better than the studentsâ understanding of mathematical concepts by applying conventional learning.